FAKTOR INDIVIDU, FAKTOR LINGKUNGAN DAN KEKURANGAN ENERGI KRONIS (KEK) PADA IBU HAMIL DI PUSKESMAS MENGWI I - Ni Wayan Eka Krisna Putri; A.A. Ngurah Kusumajaya; Ni Nyoman Astika Dewi (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
The nutritional status of pregnant women is one indicator in measuring the nutritional status of the community. If the input of nutrition for pregnant women from food is not balanced with the needs of the body there will be a deficiency of nutrients. Chronic energy deficiency can occur in women of childbearing age and in pregnant women. A person is said to suffer the risk of Chronic Energy Deficiency when the Upper Arm Circumference is 23.5 cm. The purpose of this study was to determine the relationship between individual factors and environmental factors that affect the lack of chronic energy (kek) in the Mengwi I Public Health Center. This type of research was observational with a cross-sectional design. The sample obtained was 57 pregnant women. Statistical tests using chi-square. Age of risky pregnant women is 7 people (12.3%). Low maternal education is 14 people (24.6%). The work of pregnant women who work is 37 people (64.9%). The family income of pregnant women UMR is 28 people (49.1%). There were 10 pregnant women (17.5%). Parity pregnant with a multipara category of 20 people (35.1%). Pregnant women with less attitudes as many as 26 people (45.6%). Pregnant women who behave less as many as 38 people (66.7%). Pregnant women with less family support are 29 people (50.9%). On all individual factor variables and environmental factors that affect the health of pregnant women p value α (p 0.05), which means there is no relationship between maternal age and mortality, education with income, employment with income, income with income, parity with kek, attitude with kek, and family support with kek.Keywords: Individual, Enviromental Factors, Chronic energy deficiency